"Something Wicked This Way Comes": Machiavelli, Macbeth, and the Conquest of Fortuna. Issue 4 (28th September 2016) - Zuckert, Michael P.
Abstract: As in all or almost all Shakespeare plays the opening scenes of Macbeth are key to setting up the problem the play addresses. In his Scottish play Shakespeare uses the opening scenes to set the two main contexts in which the regicide, usurpation, tyranny, and fall of the tyrant occur. The two are, we might say, the earthly or political context and the cosmic or superhuman context represented by the witches. In presenting these two contexts Shakespeare appears to be engaging in a dialogue with Machiavelli's Prince, taking cues from Machiavelli's political analysis on how to understand the political character of Scotland and taking issue with Machiavelli's ultimate agenda of a conquest of Fortuna.